Uppfinningsfrågor och uppfinningstankar – bedömningen av uppfinningshöjd och det patenträttsliga skyddsomfånget i ljuset av praxis från EPO och UPC - Isaksson,Maja (2025)
This thesis examines the inventive step criterion in Swedish patent law. The main issues addressed are what this criterion entails and how it has been applied by Swedish courts, how the inventive step assessments of the EPO and UPC differ, and what significance the UPC’s method for determining inventive step may have for Swedish legal practice in the future. These questions are explored through an analysis of case law from the Swedish Supreme Court, the EPO’s Enlarged Board of Appeal, the UPC’s Court of Appeal, and the Swedish Patent and Market Court of Appeal (PMÖD). To achieve the objectives, a pluralistic legal-dogmatic approach as described by Ramberg is applied, with PMÖD case law used to examine the legal situation in 2025. The thesis finds that it has long been established in Swedish patent law, through case law from the Swedish Supreme Court and the former Regeringsrätten, that the case law of the EPO’s Boards of Appeal is guiding for Swedish courts, and that the Swedish assessment of inventive step should reflect the problem/solution approach used by the EPO. According to this method, inventive step is assessed through a three-step process: first, identifying the closest prior art; second, formulating the objective technical problem that the invention seeks to solve; and third, determining whether the invention would have been obvious to a person skilled in the art. The establishment of the UPC raises questions about which instance, EPO or UPC, should take precedence in Swedish law to the extent that their methods for assessing inventive step diverges. In the Amgen and Edwards cases, the UPC has determined that it will not follow the EPO’s problem/solution approach in its assessment of inventive step. Instead, a more holistic evaluation should be applied, based on a starting point considered realistic for the skilled person rather than the closest prior art. The EPO’s Enlarged Board of Appeal has, in case G 1/24, shown tendencies to adapt to UPC practice in order to maintain harmonisation within the unitary patent system. It remains to be seen whether the EPO will adopt the same approach regarding the method for assessing inventive step. The problem/solution method has been applied consistently by PMÖD in 2025, regardless of technical field. No significant change in Swedish legal practice following the UPC rulings in Amgen and Edwards can be observed. This may be influenced by if, and to what extent, the EPO considers UPC case law. Both the EPO and the UPC have noted that there may be multiple ways to apply the inventive step requirement under the EPC, suggesting that both methods may become established in the field going forward. The use of different methods within the same patent system can create uncertainty about the conditions under which a patent will be granted and maintained. Clear and predictable criteria for assessing inventive step are therefore important from a legal certainty perspective.
Keywords: Immaterialrätt; Patenträtt; Uppfinningshöjd; Uppfinningstanke; UPC; EPO; EPC; Domstolsavtalet; Problem/lösningsmetoden; NJA 2000 s. 497; NJA 2002 s. 660; Amgen v. Sanofi; Meril v. Edwards; G 1/24